PENDEKATAN RME UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 9 SUNGAI PENUH - Sari, Annisa Nilam; Yarman, Yarman (Jurnal Edukasi dan Penelitian Matematika, 2024)
In a classroom, students are challenged to think and reason about mathematics. Therefore, mathematical communication skills are an essential feature as students express the result of their thinking orally and in writing. Based on observations, this skill is still not well-mastered by VIII grade students SMPN 9 Sungai Penuh. The solution is expected to be achieved by implementing the RME approach. This research objective is to describe the development and compare whether the mathematical communication skills of students who are instructed by the RME are better than direct learning. This is a quasi-experimental and descriptive research with a Nonequivalent Posttest-Only Control Group Design. The saturated sampling was used to select class VIII B as the experimental group and as the descriptive subject, while class VIII A was selected as the control group. There was an improvement in these skills based on the quiz for each indicator, except for the indicator of explaining mathematical ideas, situations, and relationships in writing using pictures, graphs, and algebra. The posttest used t-test analysis, it was found that the mathematical communication skills of the students who were instructed by using the RME were better than direct learning. Consequently, The RME effects on mathematical communication skills.Keywords – Mathematical Communication Skills, Realistic Mathematics Education, Direct Learning.